Export Growth, Capital Structure Strategy, And Corporate Competitiveness: Empirical Evidence From The Indonesian Household Products Subsector - Anwar; Abdul Rahman; Deddy Ibrahim Rauf (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study aims to analyze the influence of export growth and capital structure on the profitability of non-durable household products sub-sector companies listed on the Indonesia Stock Exchange during the research period. Profitability remains a crucial indicator of corporate financial performance, especially for manufacturing companies that rely on both domestic and international market dynamics. Export growth is considered an essential driver of revenue expansion, while capital structure reflects financial policy decisions that balance debt and equity financing in accordance with the trade-off theory. To address this objective, the research employs a quantitative approach supported by multiple linear regression analysis processed using SPSS version 26. The sample was selected using a purposive sampling technique based on specific criteria relevant to the study. The results of the simultaneous F-test show that export growth and capital structure collectively do not have a statistically significant impact on profitability. This is reinforced by the coefficient of determination (R²) of 0.111, indicating that the two independent variables explain only 11.1% of the variation in profitability, while the remaining 88.9% is influenced by other internal and external factors not included in the model. These findings suggest that although export activity and financial leverage policies contribute to corporate financial outcomes, their influence is relatively weak in this specific industrial sub-sector. Therefore, companies should consider additional strategic, operational, and market variables to enhance profitability more effectively in the competitive global market environment.